Empowering Waste Use: Eco Enzyme for Dish Soap and Fertilizer Production - Wahyuni, Sri Endang; Putri, Delia Achadina; Suharmanto, Puji (UPT Publikasi Ilmiah UNISBA, 2025)
Community service activities have been carried out for PKK mothers in RT.008 RW.04, Kebagusan, Pasar Minggu, South Jakarta, with the aim of utilizing vegetable waste and fruit peels into Eco Enzyme that can be used as multifunctional liquids, such as dishwashing soap and organic fertilizers. Activities include socialization and training on the importance of Eco Enzyme, how to make them, and their use. Organic waste that is often wasted has the potential to pollute the environment if it rots. In this training, participants are taught to process vegetable waste and become useful Eco Enzyme. The results of questionnaire respondents showed an increase in knowledge and skills from 68% to 93% as shown by participants who understood the material well and were enthusiastic about practicing it, because the materials are easy to obtain and the manufacturing process is simple.